Some Dynamic Characteristics of Binary Near-Earth Asteroids - Ivanenko, N.V.; Bazyey О.A. (Science and Innovation, 2024)
Tidal acceleration exerted by the terrestrial planets and Jupiter’s are determined, orbital resonances to evaluate the motion stability in binary asteroid systems are calculated. Radius of the Hill sphere surrounding the main component in approximation of the planetary three-body problem — the Sun-main component-satellite is calculated. Escape velocities from the surface of the asteroid satellites are found and the conclusion on the possibility of substance loss is made.